Andean labour law - Vilar Rubiano, Fabián Enrique (DIXI, 2021)
The Andean Integration System (AIS) is composed of more than ten organizations distributed in different countries that develop various topics. In each of these organizations, missions in favor of integration are put into practice. In this way, sui generis working relationships are developed which, due to their difficulty of execution, have a high possibility of ending in controversies, which must be resolved in an adequate manner so that they do not affect the mission of the entity and the coordination between the system in general. This article will preliminarily address the relationship between international labor law and domestic labor law in the framework of the ais in order to deepen through controversies the analysis of their relationship with the common principles within the scope of the International Labor Organization (ILO).